(untitled) (Edad Media. Revista de Historia, 2018)
In this article, there will be an analysis of the competition for preaching and the salvation of souls carried out by the mendicant orders, and especially by the Order of Preachers, in three urban spaces, namely, Zamora, Toro, and Benavente, during the late Middle Ages. As a result, a varied conflictive typology may be observed, including the confrontation between different orders, in this case, the Order of Friars Minors and the Order of Preachers, as well as the general conflict that developed between friars and secular clergy around leading the pastoral of believers, which in the case of Zamora shows particular characteristics.